The Effect of Internal Control Systems on Fraud Prevention in BUMDes - Saverius Salvan Elfrid Pio; Viktorianus Ompot; Annisah Febriana (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Purpose – This study investigates the effect of the system internal control on fraud prevention in the financial management of Village-Owned Enterprises (BUMDes) in Manggarai Regency. Design/methodology/approach – A quantitative approach was employed with a survey of 80 BUMDes administrators selected using purposive sampling. Data were gathered using a five-point Likert scale questionnaire and analyzed through statistics descriptive, validity and reliability tests, simple linear regression, t-tests, and the coefficient of determination (R²). The regression analysis produced the equation ????= 12.481 + 0.684 X, with a regression coefficient (????) of 0.684, a t-value of 6.918, a significance level (p-value) of 0.000, and an R2 value of 0.381. Finding/Results – The findings demonstrate that the system internal control exerts a positive and significant influence on fraud prevention in BUMDes financial management. The effectiveness of internal control, particularly in control activities and monitoring, enhances the capacity of BUMDes to deter fraudulent practices. The results indicate that the internal control system explains 38.1% of the variance in fraud prevention, while the remainder is attributable to factors such as human resource competence, organizational culture, and whistleblowing mechanisms. Originality/Value – This study contributes empirical evidence from Eastern Indonesia, an area that has received limited scholarly attention, and provides quantifiable insight into the magnitude of the relationship between internal control and fraud prevention in the context of rural enterprise governance. The research further highlights specific elements of internal control that are most impactful, offering practical guidance for policymakers and BUMDes management aiming to strengthen accountability and governance structures.